Communication Styles at Purbaya Elderly School in Salatiga in Sustaining the Potential of Older Adults - Lahade, Ruth Anggraeni Putri; Hafiar, Hanny; Mirawati, Ira (GoAcademica Research & Publishing, 2025)
The growing elderly population in Indonesia underscores the importance of improving quality of life, particularly in social and psychological aspects. Elderly Schools (Sekolah Lansia) have emerged as a non-formal educational innovation aimed at fostering SMART older adults those who are Healthy, Independent, Active, Productive, and Dignified. This study aims to analyze the communication styles employed at the Purbaya Elderly School in Salatiga in sustaining the potential of elderly students. Using a constructivist qualitative approach, data were collected through observation and interviews with facilitators and elderly participants. The findings indicate that an equalitarian communication style is predominantly applied one that emphasizes equality, openness, and mutual respect. Facilitators position themselves as learning companions rather than authoritative instructors, creating a relaxed, cheerful, and inclusive atmosphere. Polite and familiar language, the use of light humor, and a friendly tone enhance elderly engagement in the classroom. Elderly participants are given space to share experiences, engage in discussions, and remain socially and intellectually active. This equality-based communication style has proven effective in reactivating the potential of older adults, boosting their self-confidence, and challenging stereotypes that portray the elderly as unproductive. Through appropriate communication strategies, elderly schools serve as meaningful spaces for the empowerment of older adults.